MANIFESTATION OF THEOSOPHICAL PERSPECTIVE IN THE PROCESS OF GAINING SELF- DISCOVERY IN PAULO COELHO’S ALEPH - SARI, RATNA CANDRA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Existentialism proposes the idea that human being has to define his own life. Existentialism as a universal element in all thinking is the attempt of man to describe his existence and its conflicts. Human is said to have existential crisis when he is filled with the question of what is his true essence as a human being in the contemporary world. This problem however is able to encourage him to seek for the solution. Since each individual has his own way to solve his problem, this study analyzes the effort of facing existential crisis in Aleph, an autobiographical novel by Paulo Coelho which manifests his theosophical perspective. Related to this case, this study aims to describe the portrayal of Coelho’s existential crisis and to analyze the portrayal of Coelho’s theosophical perspective as part of the process of gaining self- discovery. This study uses qualitative approach particularly literary study to analyze phenomena related with the problem in the novel.This study reveals that Aleph portrays Coelho’s existential crisis and theosophical perspective and also the manifestation of the interrelated ideas between existentialism and theosophy by taking the similar concepts which cover the importance of self- awareness, to act, and the aim to achieve something that can improve one’s quality of being an authentic human.It is suggested that the next researchers to do deeper study and analysis in connection with existentialism and to relate this philosophy to biographical studies in order to broaden the critical analysis about the relationship between existentialism and the author’s biography.  Keywords: Theosophy, Self- Discovery, Existential Crisis, Paulo Coelho, Aleph